Efficient novel synthesis of pyrano[3, 2-a]- and pyrazolo[4, 3-a]-acridines. Issue 3 (1st February 2017) - Satheeshkumar, Rajendran; Kaminsky, Werner; Rajendra Prasad, Karnam Jayarampillai
ABSTRACT: The synthesis of pyrano[3, 2- a ]acridines is presented, where 7-chloro-9-phenyl-2, 3-dihydroacridin-4( 1H )-one reacts with arylaldehydes and malononitrile in the presence of piperidine in ethanol, giving with high yield via a multicomponent method. Also a new synthesis of pyrazolo[4, 3- a ]acridines is reported, where 7-chloro-9-aryl-2, 3-dihydroacridin-4( 1H )-one on Claisen condensation with ethylformate followed by hydrazine hydrate treatment through the intermediate 7-chloro-4-hydroxy-9-aryl-1, 2-dihydroacridin-3-carbaldehyde. The structures of newly synthesized compounds were deduced by spectroscopic techniques, elemental analysis, and single-crystal x-ray diffraction. GRAPHICAL ABSTRACT: